An analisys of brain drain from the social networks theory - Duque, Martha Lilia del Río (Sociedad y Economía, 2010)
Brain drain is explained through a model of decision in network, the nodes represent people with high level of education who research in their area of knowledge, and the ties describe the academic or scientific productions made with their academic couple. The scientist who hope to emigrate have to take into account the follow criteria: mean degree of scientific network, because the productivity of the scientist depend on degree of scientific collaboration developed, the utility of the different kinds of ties, the effect neighbors have on the individual productivities, the valuations of the different locations and the technology available to the scientists.